Wrongful Birth: ¿un daño resarcible en el ordenamiento jurídico colombiano? (2019)
This article seeks to answer the following research question: would it be possible to claim that in the events of the births of babies suffering from a congenital disease that involves a physical or a mental disability which went promptly unnoticed due to a prenatal diagnosis error, the parents should be awarded any kind compensation for damages provided under the Colombian legal system? In order to answer the question, the legal claim referred as wrongful birth is reviewed under the comparative law and its autonomy against other wrongful actions related to the exercise of the reproductive freedom and the responsible parenthood liberties (wrongful life, wrongful conception and wrongful adoption), based upon which, the analysis of each one of the elements of civil liability in our country is undertaken in the events of wrongful birth, to conclude its viability in Colombia and introduce a possible damage compensation scheme for this subject.